Will financial liberalization trigger the first crisis in the People's Republic of China? Lessons from cross-country experiences - Qin Gou; Yiping Huang (Asian Development Bank Institute (ADBI), 2018)
The People's Republic of China (PRC) is beginning a new wave of financial liberalization, which is necessary to support strong economic growth, but will financial liberalization lead to major financial crises, as happened in many middle-income countries? The empirical examinations conducted in this study suggest that financial liberalization generally lowers financial risks, especially for middle-income economies. Nevertheless, the pace of liberalization, quality of institutions, and regulatory structure also matter for outcomes of financial instability. From these findings, we draw some policy implications for the PRC: (1) further liberalization is important not only for economic growth but also for financial stability; (2) a gradual liberalization approach should work better, focusing on the sequencing of reforms; (3) the quality of institutions, especially strong market discipline, is also important for containing financial risks; and (4) it is better for the central bank to participate in financial regulation.
Keywords: G01; G18; 330; financial liberalization; financial crisis; financial instability